KELIMPAHAN DAN KEKAYAAN ARTROPODA PREDATOR PADA TANAMAN PADI YANG DIAPLIKASI BIOINSEKTISIDA BACILLUS THURINGIENSIS - Chandra Irsan; Fina Sunariah; Siti Herlinda; Yuanita Windusari (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2016)
Abundance and species richness of the predatory arthropods on paddy treated with Bacillus thuringiensis bioinsecticide.Â Application of bioinsecticide from bacterial entomopathogen has not been reported yet that can decrease abundance and species richness of predatory arthropods, such as spiders and predatory insects. This research was aimed to analyze the abundance and species richness of predatory arthropods paddy fields applied by B. thuringiensis bioinsecticide on paddy in fresh swamp area. Areas observed were 2 ha paddy fieldâ€™s at Situ Bagendit variety. Predatory arthropods inhabiting canopy were sampled using sweep but soil dwelling arthropods were trapped using pitfall traps. The result showed that abundance of spiders inhabiting canopy decreased significantly after B. thuringiensis bioinsecticide application on paddy compared to control without bioinsecticide but the abundance of predatory insects were not significantly affected by the bioinsecticide. Application of the bioinsecticide did not significantly affect the abundance and species richness of soil dwelling predatory arthropods, such as spiders and predatory insects.